'A Tortured Nation Gave Birth to a Lunatic': The Construction of Insanity in the 1912 Terrorist Attack in Croatia. (19th July 2019) - Fatović-Ferenčić, Stella; Kuhar, Martin
Summary: In spring 1912, 25-year-old lawyer Luka Jukić tried to assassinate the Croatian Ban and Royal Commissioner Slavko Cuvaj. This article focuses on several aspects of the trial against Jukić: first, on analysing the impact of Cesare Lombroso's criminology in Croatia; second, on the testimony by forensic psychiatrist Ivo Žirovčić, who controversially claimed that Jukić was sane; third, on unmasking the techniques and manipulations by the media, the regime and the opposition concerning the assassin's alleged insanity; and finally, on identifying the ways in which the case influenced further political and revolutionary activities in the country. The discussion concerning Jukić's accountability deepened the chasm between the supporters and opponents of Cuvaj's regime, both in the political sphere and within the Croatian medical community.